A chromosome‐level genome assembly of Pyropia haitanensis (Bangiales, Rhodophyta). (12th November 2019) - Cao, Min; Xu, Kuipeng; Yu, Xinzi; Bi, Guiqi; Liu, Yang; Kong, Fanna; Sun, Peipei; Tang, Xianghai; Du, Guoying; Ge, Yuan; Wang, Dongmei; Mao, Yunxiang
Abstract: Pyropia haitanensis (Bangiales, Rhodophyta), a major economically important marine crop, is also considered as an ideal research model of Rhodophyta to address several major biological questions such as sexual reproduction and adaptation to intertidal abiotic stresses. However, comparative genomic analysis to decipher the underlying molecular mechanisms is hindered by the lack of high‐quality genome information. Therefore, we integrated sequencing data from Illumina short‐read sequencing, PacBio single‐molecule sequencing and BioNano optical genome mapping. The assembled genome was approximately 53.3 Mb with an average GC% of 67.9%. The contig N50 and scaffold N50 were 510.3 kb and 5.8 Mb, respectively. Additionally, 10 superscaffolds representing 80.9% of the total assembly (42.7 Mb) were anchored and orientated to the 5 linkage groups based on markers and genetic distance; this outcome is consistent with the karyotype of five chromosomes ( n  = 5) based on cytological observation in P. haitanensis . Approximately 9.6% and 14.6% of the genomic region were interspersed repeat and tandem repeat elements, respectively. Based on full‐length transcriptome data generated by PacBio, 10, 903 protein‐coding genes were identified. The construction of a genome‐wide phylogenetic tree demonstrated that the divergence time of P. haitanensis and Porphyra umbilicalis was ~204.4 Ma. Interspecies comparison revealed that 493 gene families were expanded and that 449 were contracted in the P. haitanensis genome compared with those in the Po. umbilicalis genome. The genome identified is of great value for further research on the genome evolution of red algae and genetic adaptation to intertidal stresses.